Marijuana use and serum testosterone concentrations among U.S. males. (10th April 2017) - Thistle, J. E.; Graubard, B. I.; Braunlin, M.; Vesper, H.; Trabert, B.; Cook, M. B.; McGlynn, K. A.
Summary: Marijuana has been reported to have several effects on the male reproductive system. Marijuana has previously been linked to reduced adult testosterone, however, a study in Denmark reported increased testosterone concentrations among marijuana users. This study was performed to estimate the effect of marijuana use on testosterone in U.S. males. Data on serum testosterone, marijuana use, and covariates for 1577 men from the 2011–2012 U.S. National Health and Nutrition Examination Survey (NHANES) were analyzed. Information on marijuana use was collected by a self‐administered computer‐assisted questionnaire. Serum testosterone was determined using isotope dilution liquid chromatography tandem mass spectrometry. The effects of marijuana use on serum testosterone concentrations were examined by frequency, duration, and recency of use. Adjusted means and 95% confidence intervals (CI) of serum testosterone across levels of marijuana use were estimated using multiple linear regression weighted by the survey weights. The majority (66.2%) of the weighted study population reported ever using marijuana with 26.6% reporting current marijuana use. There was no difference in serum testosterone between ever users (adjusted mean = 3.69 ng/mL, 95% CI: 3.46, 3.93) and never users (adjusted mean = 3.70 ng/mL, 95% CI: 3.45, 3.98) upon multivariable analysis. However, serum testosterone was inversely associated with time since last regular use of marijuana ( p‐ value for trend = 0.02). When restricted to men aged 18–29 years, this relationship strengthened ( p‐ value for trend <0.01), and serum testosterone was also inversely associated with time since last use ( p‐ value for trend <0.01), indicating that recency of use, and not duration or frequency, had the strongest relationship with testosterone levels. Serum testosterone concentrations were higher in men with more recent marijuana use. Studies are needed to determine the extent to which circulating testosterone concentrations mediate the relationship of marijuana use with male reproductive outcomes.